Digital Marketing Design and Content Development at Nutrihub Lampung - Chaniago, Nicco Chaisar; Saputra, Aditia Jaya; Calosa, America Rachmasari; Dewi, Ayu Karmila; Akuan, Muhammad Farel; Kholifah, Nurul; Bangsawan, Satria (Devotion: Journal Corner of Community Service, 2023)
A large number of internet users in Indonesia is an opportunity for business people to use digital marketing to get consumers. Nutrifood is a company engaged in the healthy food and beverage industry and has a place for public activities called Nutrihub. This service examines how Nutrihub uses digital content to build brand awareness. The dedication method used comes from devotion and conducting focus group discussions (FGD) with the leaders and employees of Nutrihub Lampung. The data obtained is then processed based on selection and sorting so that it is sorted, which is more appropriate in describing the problem according to the purpose of the service. The data sources used are journals, publications, websites, and Nutrihub's social media pages. The service results show that using digital content as marketing, including websites, e-commerce and social media, using the slogan "Connect, Collaborate, Innovate," is considered successful in building brand awareness at Nutrihub Lampung. Because it can build people's top of mind that Nutrihub is a brand of healthy living through a series of high-tasting health food and drink products. Instagram social media and e-commerce platforms have a big factor in building Nutrihub's brand awareness in the eyes of the public.